2013
DOI: 10.1161/hypertensionaha.111.00617
|View full text |Cite
|
Sign up to set email alerts
|

Central Pulse Pressure Is an Independent Determinant of Vascular Remodeling in the Retinal Circulation

Abstract: A lthough the importance of hypertension as predictor of coronary heart disease and stroke has been known for a long time, the relative contribution of the individual components of peripheral blood pressure (BP) to the development of cardiovascular (CV) disease is still a matter of debate. [1][2][3][4][5] More striking nowadays, the importance of central hemodynamics is more and more acknowledged. Pathophysiologically, it seems consistent that the estimation of the central pressure in the aorta, which is actua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 45 publications
2
35
0
Order By: Relevance
“…Alternatively, abnormalities in small artery structure could increase mean BP, which, in turn, increases shear stress and hence arterial stiffness of large arteries, creating a vicious cycle. 34,35 The correlation between remodeling of retinal arterioles and aortic central systolic or pulse pressure, observed in our study, confirms previous findings, 13 but lost significance when 24-hour BP was taken into consideration, indicating that the 24-hour pressure load may be a stronger determinant of changes in microvasculature than a single measurement of aortic central pressure. A possible explanation, as compared with previous findings, 14 may be related to the in vivo evaluation of retinal arterioles, which does not allow to completely separate structural from functional characteristics, 10 whereas the more invasive micromyographic technique clearly identifies the eutrophic or hypertrophic increase in small artery wall thickness.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Alternatively, abnormalities in small artery structure could increase mean BP, which, in turn, increases shear stress and hence arterial stiffness of large arteries, creating a vicious cycle. 34,35 The correlation between remodeling of retinal arterioles and aortic central systolic or pulse pressure, observed in our study, confirms previous findings, 13 but lost significance when 24-hour BP was taken into consideration, indicating that the 24-hour pressure load may be a stronger determinant of changes in microvasculature than a single measurement of aortic central pressure. A possible explanation, as compared with previous findings, 14 may be related to the in vivo evaluation of retinal arterioles, which does not allow to completely separate structural from functional characteristics, 10 whereas the more invasive micromyographic technique clearly identifies the eutrophic or hypertrophic increase in small artery wall thickness.…”
Section: Discussionsupporting
confidence: 91%
“…Central BP, indicative of changes in large conduit arteries, was found to be an independent determinant of vascular remodeling in retinal arterioles, 13 supporting the concept that changes in macrovasculature and microvasculature are strongly interrelated and confirming previous results obtained with invasive assessment of small artery remodeling by micromyography. 14 Because the possible interrelationship between alterations in retinal arterioles and 24-hour BP has not been extensively evaluated and because the influence of ambulatory BP monitoring in respect to peripheral and central hemodynamics on retinal structure deserves further investigation, we considered worthwhile assessing the relationship of WLR of retinal arterioles with clinic brachial and 24-hour ambulatory BP and with central BP in normotensive subjects and in patients with primary hypertension.…”
supporting
confidence: 87%
“…7,[13][14][15] Moreover, an association between CPP and retinal disease was recently reported. 16 We have previously found 24-hour measurements of CASP and CPP obtained with a different device (BPro, HealthStats, Singapore) to be associated with diabetic complications (albuminuria degree, presence of CVD, retinopathy, and autonomic dysfunction) in this cohort. 10 With this study, we found no association between central hemodynamics and retinopathy but a significant association with presence of autonomic neuropathy (heart rate variability during deep breathing; data not shown).…”
Section: Discussionmentioning
confidence: 69%
“…32 Among adults, a crosssectional study among 135 individuals showed that arterial stiffness measured by central pulse pressure was inversely correlated with wall-tolumen ratio of retinal arterioles. 33 Another study among 197 adults found that retinal arteriolar narrowing was associated with higher carotidfemoral pulse wave velocity. 34 No previous study in children examined the associations of retinal vessel calibers with carotid-femoral pulse wave velocity.…”
Section: Figurementioning
confidence: 99%